Implementation of Sustainable Agricultural Land Transfer Policy in Sidrap Regency - Rika Rika; Ihyani Malik; Burhanuddin Burhanuddin; Fatmawati A Mappasere (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
Agricultural land conversion is a crucial issue in facing the challenges of food security and natural resource conservation. Sidrap District, as one of the agricultural regions in Indonesia, faces significant pressure related to agricultural land conversion. Therefore, the implementation of local government supervision policies is very important. This research aims to analyse the implementation of local government supervision policies on agricultural land conversion in Sidrap Regency. This research uses a qualitative method with data sources from interviews, documentation, and observation. The data of this study used Nvivo 12 Plus to obtain relevant analyses. The findings of this study show that in the implementation of the policy to monitor the conversion of agricultural land in Sidrap District, there are two main approaches, namely preventive and repressive approaches, which work together to maintain the integrity of agricultural land. The preventive approach focuses on prevention efforts, while the repressive approach aims to enforce regulations with appropriate sanctions. In addition, determinant factors such as communication, resources, disposition and bureaucratic structure also play a crucial role in this overall process. With a holistic effort involving effective coordination between relevant agencies and improvements to these determinant factors, Sidrap district has the potential to maintain agricultural sustainability and food security in the future.